(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Consistent involvement in sports-related pursuits enhances both psychophysiological health and social wellbeing. This study investigated the psychological pathways through which physical activity contributes to life satisfaction, focusing specifically on the mediating role of dispositional self-control. While the positive impact of physical activity on wellbeing is well documented, little is known about the psychological mechanisms behind this relationship, especially in relation to activity levels recommended by the World Health Organization. Drawing on prior findings on the interplay between self-regulation and wellbeing, we hypothesised that dispositional self-control would mediate the relationship between physical activity and life satisfaction, particularly at higher engagement levels. Methods: The Satisfaction with Life Scale and the Brief Self-Control Scale were completed by 282 respondents (mean age = 23.2, standard deviation = 8.4). The participants also self-reported their average weekly minutes of physical activity over the past year. Based on WHO guidelines, they were categorised into four levels of physical activity. Mediation analyses were conducted to examine the indirect effects of physical activity on life satisfaction using self-control as a mediating variable. Results: The effect of high-level physical activity (exceeding WHO recommendations) on life satisfaction was significantly mediated by dispositional self-control (estimate = 0.37; 95% confidence interval (CI) = 0.14; 0.59; β = 0.09). In contrast, the indirect effects were not significant for standard-level physical activity (meeting WHO recommendations; estimate = 0.08; β = 0.03) or low-level physical activity, which included both inactive individuals and those engaging below WHO standards (estimate = 0.16; β = 0.05). The full mediation model accounted for 19.7% of variance in life satisfaction. Only high physical activity levels had a significant indirect effect on life satisfaction through higher self-control. Conclusion: This study highlights dispositional self-control as a key psychological mechanism connecting physical activity and life satisfaction, suggesting that health promotion strategies should emphasise consistent and high-level physical engagement. Our findings underscore the importance of meeting or exceeding WHO physical activity guidelines to promote not only physical health but also psychological wellbeing. Interventions aimed at enhancing mental health and subjective wellbeing through physical activity may benefit from a focus on the development of self-regulatory capacities fostered by regular exercise.